A study on the effectiveness and acceptance of the camouflage vs. the standard anesthetic syringe - Paras, Allea T.
The researcher wanted to determine the effectiveness and acceptance of the camouflage vs. the standard anesthetic syringe among the 4-13 year old children from the Department of Social Welfare and Development (DSWD) - Reception and Study Center in Angeles City. The effectiveness of the camouflage vs. the standard anesthetic syringe was determined using the Venham picture test, heart rate, cooperative behavioral and clinical anxiety rating. Acceptance of the camouflage syringe was assessed by the number of children that allowed the pseudo injection procedure to take place. P value (one tail) was used to determine the effectiveness of the camouflage syringe while chi square value was computed to determine its acceptance. The picture test, clinical anxiety and cooperative behavioral rating reported a significant increase in anxiety in the standard syringe than in the camouflage syringe. There was no difference in heart rate from the standard to the camouflage syringe. Both syringe were accepted. In conclusion, the camouflage syringe is effective in lowering anxiety of the children. It is also accepted among the children.